Identification of CD8+CD25+Foxp3+ suppressive T cells in colorectal cancer tissue. Issue 4 (20th November 2008) - Chaput, N; Louafi, S; Bardier, A; Charlotte, F; Vaillant, J-C; Ménégaux, F; Rosenzwajg, M; Lemoine, F; Klatzmann, D; Taieb, J
Abstract : Background: The antitumoral immune response is one determinant of colorectal cancer (CRC) outcome. Recent work suggests that Foxp3 + CD25 + CD4 + regulatory T cells (T4reg) might hamper effective immunosurveillance of emerging cancer cells and impede effective immune responses to established tumours. In this descriptive study, we analysed blood and tissue regulatory T cell populations in patients with CRC. Methods: Blood and tissue regulatory Foxp3 + T cells from 40 patients with CRC were compared to regulatory Foxp3 + T cells from normal colonic tissue and from blood of 26 healthy volunteers. Flow cytometry was used to quantify and phenotype all Foxp3 + T cell populations. Correlations were sought with the tumour stage and with micro-invasive status. The suppressive capacity of regulatory Foxp3 + T cells was assessed by their effect on CD4 + CD25 − T cell proliferation in vitro and by their capacity to inhibit cytokine production by conventional T cells. Results: We found a significant increase of CD8 + CD25 + Foxp3 + cells (T8reg) in blood and CRC tissue; their phenotype was close to that of T4reg. T8reg cells infiltrating CRC were activated, as suggested by increased cytoxic T lymphocyte-associated antigen-4, glucocorticoid-induced tumour necrosis factor-related protein, and transforming growth factor (TGF)β1 expression compared to T8reg from normal autologous colonic tissue. Moreover, T8reg were able to suppress CD4 + CD25 − T cell proliferation and Th1 cytokine production ex vivo, demonstrating that tumour-infiltrating T8reg have strong suppressive capacities. T8reg numbers correlated with the tumour stage and with micro-invasive status. Finally, interleukin 6 and TGFβ1 synergistically induced the generation of CD8 + CD25 + Foxp3 + T cells ex vivo. Conclusions: We have identified a new regulatory T cell population (CD8 + Foxp3 + ) in colorectal tumours. After isolation from cancer tissue these CD8 + Foxp3 + cells demonstrated strong immunosuppressive properties in vitro. These data suggest that these cells may contribute to tumoral immune escape and disease progression.